Revealing the biodiversity and the response of pathogen to a combined use of procymidone and thiamethoxam in tomatoes. (30th June 2019) - Lin, Shaohua; Han, Yingyan; Jiangyuan, Chunzi; Luo, Yunbo; Xu, Wentao; Luo, Hongxia; Pang, Guofang
Highlights: Dissipation of procymidone and thiamethoxam was affected by their combined use. Pre-harvest interval for combined use of procymidone and thiamethoxam was delayed. The dissipation of procymidone and thiamethoxam affected microbial diversity. The genus Escherichia-Shigella was responsed to the concentration of procymidone. Abstract: The dissipation kinetics of a combined use of procymidone and thiamethoxam, and their impact on the biodiversity and pathogen on surface of tomatoes were studied. The half-lives of procymidone and thiamethoxam, used either on their own or in combination with each other, were 2.94 or 3.26 days and 2.41 or 2.67 days, respectively. The residues dropped below the maximum residue limit (MRL) after 7 or 10 days (MRL 2 mg·kg −1 for procymidone), and 10 or 14 days (MRL 0.2 mg·kg −1 for thiamethoxam), respectively. The phylum Bacteroidetes, Cyanobacteria, and Proteobacteria, were dominantly present in all studied samples. The genus Escherichia-Shigella was found and exposed to the dissipation of procymidone (r = −0.9209 for procymidone on its own, and r = −0.8611 for procymidone in combination with thiamethoxam). These results will contribute to establish adequate monitoring of pesticides residues and their incorporation in surface ecology and pathogen management strategies in tomatoes.